Economics - Stiglitz, Joseph E.; Walsh, Carl E. (New York, 2006)
For the fourth edition of this innovative textbook, 2001 Nobel Prize winner Joseph E. Stiglitz again joins forces with top monetary economist, Carl E. Walsh. Together, they integrate contemporary economics into the traditional curriculum. Highlights are the continued coverage of the economics of information and imperfect markets, and the emphasis is on the critical role of capital markets in the macro economy.
Keywords: Economics